STUDI KORELASI PENERAPAN METODE DISKUSI DENGAN MOTIVASI BELAJAR FIQIH SISWA MA AL-ISHLAH SENDANGAGUNG : STUDI KORELASI PENERAPAN METODE DISKUSI DENGAN MOTIVASI BELAJAR FIQIH SISWA MA AL-ISHLAH SENDANGAGUNG - Zakhiru Rahma Zaha (Jurnal Penelitian dan Pendidikan, 2023)
The background is that teaching activities are nothing but what the teacher must achieve is how students can master the lesson material that has been delivered, one of which is by developing discussion methods. Through the application of the discussion method, it is hoped that students are encouraged to be actively involved in the learning process at school, can be stimulated to think critically and rationally or objectively in solving a problem so that learning objectives can be achieved. With the discussion method students are active in learning. The research that the author did was included in the category of qualitative descriptive research using the methods of observation, interviews, and documentation. And for the type of research used is classroom action research or in English called Classroom Action Research. The results of the research conducted by the author can be concluded that the correlation between the application of the discussion method and the learning motivation of FIQIH is included in the good category, because the results of observations and correlation analysis show a significant relationship, thus the hypothesis that the author proposes is accepted and there is a significant relationship, and the discussion method is one of the methods used in Fiqh learning and can increase student motivation at MA AL-ISHLAH Sendangagung Paciran Lamongan.